2021
DOI: 10.3389/fpsyt.2021.654120
|View full text |Cite
|
Sign up to set email alerts
|

Latent Structure of Combined Autistic and ADHD Symptoms in Clinical and General Population Samples: A Scoping Review

Abstract: Background: Many phenotypic studies have estimated the degree of comorbidity between Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD), but few have examined the latent, or unobserved, structure of combined ASD and ADHD symptoms. This is an important perquisite toward better understanding the overlap between ASD and ADHD.Methods: We conducted a scoping review of studies that examined the factor or latent class structure of ASD and ADHD symptoms within the same clinical or gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
(165 reference statements)
0
4
0
Order By: Relevance
“…Some studies which included a comorbid group found greater deficits in the comorbid group compared to the ASD, ADHD and typically developing groups (Antshel & Russo, 2019;Craig et al, 2016;Hwang-Gu et al, 2019). These studies do not clarify whether EFs are associated with ASD or ADHD or whether the comorbid group represents a distinct diagnostic entity (Caron & Rutter, 1991;Krakowski et al, 2021). Studies in which ADHD and ASD traits were controlled indicate that, at least response inhibition and response variability, may be more strongly associated with ADHD than with ASD traits (Karalunas et al, 2018;Schachar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies which included a comorbid group found greater deficits in the comorbid group compared to the ASD, ADHD and typically developing groups (Antshel & Russo, 2019;Craig et al, 2016;Hwang-Gu et al, 2019). These studies do not clarify whether EFs are associated with ASD or ADHD or whether the comorbid group represents a distinct diagnostic entity (Caron & Rutter, 1991;Krakowski et al, 2021). Studies in which ADHD and ASD traits were controlled indicate that, at least response inhibition and response variability, may be more strongly associated with ADHD than with ASD traits (Karalunas et al, 2018;Schachar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Methodological differences in recruitment, measurement, and analysis mean that many results are only comparable to findings derived from analytical techniques of the same class. For example, Krakowski et al (2021) highlighted in their scoping review that the latent class studies often identified more phenotypic overlap between autism and ADHD, whereas factor analytic studies tended to support distinct 'autism' and 'ADHD' factors. A key recommendation from their review was for future studies to employ statistical methods that combine multiple techniques together, such as factor mixture modelling (FMM).…”
Section: Introductionmentioning
confidence: 99%
“…Studies attempting to model the relationship between ADHD and autism have employed a variety of methods, including latent class analysis and factor analysis (Farhat et al., 2022 ; Krakowski et al., 2021 ). Methodological differences in recruitment, measurement, and analysis mean that many results are only comparable to findings derived from analytical techniques of the same class.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation